New onset or worsening of psoriasis following biologic therapy: A case series. (March 2017) - Bruzzese, Vincenzo; De Francesco, Vincenzo; Hassan, Cesare; Lorenzetti, Roberto; Scolieri, Palma; Marrese, Cinzia; Zullo, Angelo
Biologic therapies may cause so-called "paradoxical side-effects, " that is, the onset or exacerbation of new symptoms/diseases for which biological treatment should be effective. Among these, psoriatic skin lesions have been described. We report a case series of ten patients with either new onset (seven cases) or worsening (three cases) of psoriasis occurring during a biologic therapy. Six patients were receiving a biologic monotherapy, while four patients were in combination treatment with methotrexate (MTX). Psoriasis remission was observed in two patients who discontinued biologic therapy. In the six patients in whom biologic therapy was not discontinued, a complete disappearance or a partial improvement of skin lesions was achieved following topic steroid therapy in two patients and three patients, respectively. In the remaining patient, psoriasis developed during Adalimumab monotherapy, which completely disappeared when the Infliximab and MTX combination was started. The potential pathogenetic mechanisms were shortly reviewed.